2020
DOI: 10.21203/rs.3.rs-29281/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Iron metabolism in patients with rheumatoid arthritis

Abstract: Background. The most common haematological manifestation in RA is anaemia (30-60%). The aim of the study was the assessment of the prevalence of iron deficiency in RA patients using standard parameters and new biomarkers.Material and methods. The study was conducted on 62 RA patients, aged 52±15, treated at the Department of Internal Medicine of the 4th Military Teaching Hospital in Wrocław between 2016 and 2017. The control group comprised 58 healthy individuals, aged 56±9. The following tests were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…There was evidence of anemia, as the median values of Hb and MCV were 12 g/dL and 80 fL, respectively, indicating iron deficiency anemia that is commonly reported in patients with RA. [ 23 ] The results showed that Hb is not a predictor of QoL. Previous studies have shown a significant inverse relationship between mental health but not physical or emotional health and Hb using the Short Form (SF)-36 questionnaire.…”
Section: Discussionmentioning
confidence: 91%
“…There was evidence of anemia, as the median values of Hb and MCV were 12 g/dL and 80 fL, respectively, indicating iron deficiency anemia that is commonly reported in patients with RA. [ 23 ] The results showed that Hb is not a predictor of QoL. Previous studies have shown a significant inverse relationship between mental health but not physical or emotional health and Hb using the Short Form (SF)-36 questionnaire.…”
Section: Discussionmentioning
confidence: 91%
“…However, none of the controls with normal synovia had iron deposition. Another study found that the iron metabolism is different in RA than in general health (35). It is worth noting that iron deficiency is common (64%) in RA patients with high disease activity.…”
Section: Iron Handlingmentioning
confidence: 98%
“…In 1968, research findings had already illuminated a substantial elevation in iron content within the synovial tissue of individuals grappling with RA ( Senator and Muirden, 1968 ) More recently, scientific inquiries have unveiled a nuanced interplay involving the altered expression of iron-binding protein ferritin and diminished saturation of transferrin within the blood of RA patients ( Tański et al, 2021 ). In consequence, discernibly diminished iron levels stand in contrast to those found in the control group.…”
Section: The Roles Of Ferroptosis and Ferritinophagy In Arthritismentioning
confidence: 99%